The Effect Of Occupational Safety And Health (Osh) Promotion On Safe Behavior Among Cleaning Service Workers At The Faculty Of Medicine And Health Sciences, Universitas Jambi - Mutia Fadilla Asyifa; Dwi Noerjoedianto; M. Ridwan; Ashar Nuzulul Putra; Budi Aswin (International Journal of Health Engineering and Technology, 2026)
Workplace accidents remain a serious issue in Indonesia, with unsafe behavior being the primary contributing factor. Unsafe behavior has been identified as the primary cause of occupational accidents, contributing to approximately 88% of incidents. Preventive efforts can be carried out through Occupational Safety and Health (OSH) promotion, including communication, training, supervision, and safety signage. This study aims to analyze the relationship between OSH promotion and safe behavior among cleaning service workers at the Faculty of Medicine and Health Sciences, Universitas Jambi. This study used a quantitative approach with a cross-sectional design. The population consisted of all cleaning service workers totaling 20 respondents, and total sampling was applied. Data were collected using questionnaires and observation sheets, then analyzed using univariate and bivariate methods with the Chi-Square test at a significance level of 0.05. The results showed significant relationships between OSH communication (p = 0.024), OSH training (p = 0.014), and OSH supervision (p = 0.010) with safe behavior. The safety signage variable could not be further analyzed due to constant data. In conclusion, OSH promotion is associated with safe behavior, particularly in communication, training, and supervision aspects. The study concludes that OHS promotion significantly influences safe behavior, which in turn affects employee performance. Strengthening communication, training, and supervision is recommended to reduce workplace accidents